Autodidactic Preconditions and Levers of Activating Out-of-Auditorium Independent Student Work - Tkachuk, Hanna (Pedagogical Discourse, 2017)
Ukrainian education’s conversion, euro-integration of science and technology, educational system formation, being at high rates of continuous improvements, makes necessity to develop and optimize a methodical system of organization of beyond-class self-independent students’ work. The existing scientific, methodical, and normative materials in self-education didactics do not correspond to requirements of such projects as «Long Life Learning», distance learning, and Bologna’s initiatives, neither at scientific nor methodological and methodical levels, in order to ensure the right of nationals to receive higher education. The author suggests directing principles of auto-didactics as a self-education technology at solving the problem in organization of beyond-class self-independent students’ work. Auto-didactics as a branch of education pedagogics is a new one in pedagogical science. It also reflects a new paradigm in the higher education system. Particularly, this concerns the system of organization of beyond-class self-independent students’ work. This is a theory of self-education which has never existed before, and which opens educational space named self-learning. That allows, within national educational space, developing auto-didactics’ application in a series of separate scientific directions and specialities. First of all, scientific and methodological approaches of auto-didactics are to be directed at solving the problem in organization of beyond-class self-independent students’ work. It is proven that independent student work (ISW) is such that it bears a status of a directly expressed scientific notion, and the learning process is a function of the purpose – obtaining knowledge, acquiring and developing skills and abilities. The notion «favor actualization» is further developed as a main lever and head motivating force of ISW. Also a mechanism of initiating the actual favor is shown along with revealing an allocation of actualized favor in the space of educational matter for the subject «General chemistry», that is fulfilled for the first time. It is shown that, for development in the autodidactic system, the following ones are important: task-like approach and semester control works (exercises), complex control works (CCWs), complex control assignments (CCAs) by specialities, and also application of active teaching methods along with computer simulation of laboratorial practicum in chemistry study subjects. Key words: autodidactics, independent student work, self-education, high school didactics, educational technologies.